Alkaline hydrolysis of colorant PET waste under microwave condition - Tan, Jing Sen (Nanyang Technological University, 2022)
Economic expansion and the world’s alternating patterns of consumption and production have led to a drastic increase in polyethylene terephthalate (PET) plastic waste all over the world. The vast usage of PET plastic bottles has harmed the environment and posed a threat to human health. The recycling of polyethylene terephthalate (PET) bottles has posed many challenges and issues to our environment due to their sustainability as they became waste after usage. Although the recycling rate of PET is considerably above average, the duration of chemical depolymerization is still arguably quite long. The extensive usage of PET bottles requires a more efficient process. This study will examine the effectiveness of breaking down PET using conventional Alkaline Hydrolysis under microwave conditions. The usage of glycerol acting as a catalyst to enhance the chemical process will also be explored in this study. PET samples are prepared by cutting them into smaller pieces manually. First part of the experiment was conducted with determined parameters to carry out alkaline hydrolysis of PET flakes inside the chosen microwave machine. Results have shown that degradation do occur under microwave conditions however it did not achieve a targeted conversion of PET. Second part of the experiment was conducted with the same determined parameters except with the inclusion of glycerol. Different ratio of mixture between glycerol and distilled water with NaOH pellets were first tested to check the degradation effectiveness of PET flakes.